Related Factors With The Implementation Of Tetanus Diphtheria Immunization in Pregnant Women - Diah Triratnasari (Jurnal Berkala Epidemiologi, 2017)
The maternal and neonatal tetanus elimination program is a program that aims to evenly improve the health of mothers and children to be free from tetanus by carrying out Tetanus-Diphtheria immunization during pregnancy. In 2016, only 585 of 1073 pregnant women in the area of Public Health Centers (PHC) of Burneh Sub-District in Bangkalan District were recorded as having Tetanus-Diphtheria immunization. This study aims to analyze the factors associated with the participation of pregnant women in implementing Tetanus-Diphtheria immunization in the work area of the PHC of Burneh Sub-District in 2016. This research is a analytic study with a cross-sectional design. This research was conducted in 12 villages included in the working area of the PHC of Burneh Sub-District in 2016. The number of informants obtained was 93 people. Primary data collection techniques using interview techniques with questionnaire guidelines, while secondary data using literature studies and archive data on Tetanus-Diphtheria immunization in the PHC and the Bangkalan District Health Office. Data analysis using the chi-square test. The results of this study indicate that the majority of respondents aged 20 to 30 years, with the number of children owned by respondents mostly numbered one and the level of knowledge that is in the category of less about tetanus and Tetanus-Diphtheria immunization. There is a relationship between age (p = 0,000), level of education (p = 0,000), level of knowledge (p = 0.035), husband's support (p = 0.001), and the attitude of officers (0.001) with the implementation of tetanus immunization in the work area of PHC of Burneh Sub-District 2016. The research suggestion is the role of health workers and family is an important factor to encourage respondents to have the awareness to carry out Tetanus-Diphtheria immunization during pregnancy.